رسالة في بيان حكم إسقاط الصلاة عن الميت تأليف إبراهيم بن حسين بن أحمد بن محمد بن بيري، ت. 1099 هـ.: تحقيق ودراسة - ابن بيرى، إبراهيم بن حسين بن أحمد بن محمد، ت. 1099 هـ.; حماد، حمزة عبدالكريم محمد (جامعة أم القرى, 2019)
The letter dealing of dropping the prayers missed by the dead; the work has edited the opinion of the tap and concluded that the dead if recommended to feed him prayers or recommended prayers for him; If he does not have money, the heir does not have to do that, and if he recommends that the expiation be given to him and no money is given to him, the heir shall be given a saa' and given to a poor people. The researcher followed the method of investigating the manuscripts in this letter, comparing the view of the Hanafis with other doctrines of jurisprudence, and concluded that the opinion of the majority of doctrines of jurisprudence is most likely that whoever dies and has a prayer that is not ruled by his guardian and does not fall for him with ransom, because fasting is a ritual of fasting and there is no provision of food for the missed prayers.
هذا البحث هو تحقيق لرسالة قيمة من رسائل العلامة الشيخ إبراهيم بن حسين بن بيري الحنفي رحمه الله (ت ١٠٩٩ هـ) تتناول مسألة إسقاط الصلوات الفائتة عن الميت؛ قام المصنف فيها بتحرير رأي الحنفية وانتهى إلى أن الميت إذا أوصى بأن يطعم عنه للصلوات أو أوصى بالصلوات عنه؛ فذلك يخرج من ثلث ماله لكل صلاة نصف صاع من بر، وإن لم يكن له مال؛ لا يلزم الوارث فعل ذلك، وإن أوصى بأن يعطى كفارة صلواته ولا مال له؛ استقرض الوارث صاعا ويعطى للفقراء. وقد اتبع الباحث منهج تحقيق المخطوطات في هذه الرسالة مع مقارنة رأي الحنفية بغيره ومن المذاهب وانتهى إلى أن رأي الجمهور هو الراجح بأن من مات وعليه صلاة لم يقض عنه وليه ولا تسقط عنه بالفدية؛ لأن الصلاة عبادة توقيفية ولم يرد نص بالإطعام بدل الصلوات الفائتة.
Keywords: تحقيق المخطوطات -- الفقه الإسلامي -- فقه العبادات -- الأحكام الشرعية -- أحكام الصلاة